Nilai-Nilai Pendidikan Perempuan dalam Novel Aisyah Karya Sibel Eraslan - Ngaisah, Ngaisah (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Value as an abstract conception of something value in humans about what is considered good and bad for the object in the direction towards object in value. The emergence of education women originating from the middle east country is exactly the Arab country. Women’s education is a process of forming behavior. Women education is not only the formation of a knowledge not just a transfer of knowledge.Formal and non- formal women’s education not just a transfer of knowledge. Women’s educations maximize the potential that already exists in humans. Humans are noble beings created by God with senses and great reason.Sibel has had a great influence on the world of education. With her innovation made a famous history of women known to the world as a novel that is full of educational values should be which is relevant throughout the ages.So educational tools such as material or methods.Evaluation of educationsare required to be humane too.The method in this method used this study is literature with content analysis. Present engineering education, creates a social structure. This education covers: (1) religion education for women (religion knowledge) the first mandatory thing for women; (2) educational education is must be known by women (believe in Allah and dhikr to Allah); (3) education of morality for women; 4) Social education; 5) Family education for women.